Sine Wave Filters Design for AC Motor Drives with Genetic Algorithms - Mario Cacciato; Giuseppe Scarcella; Giacomo Scelba; Pavol Spanik (Communications - Scientific letters of the University of Zilina, 2015)
This paper proposes a suitable design methodology of the filter used at the output of inverters for AC motor drives. While it allows to achieve the best tradeoff among different design constraints that are difficult to include in standard design methods, such an approach is able to simultaneously consider several technical issues such as losses and voltage drops of the filter, total harmonic distortion of currents and voltages as well as economic aspects. Accordingly, the proposed procedure determines the optimal values of the filter parameters by exploiting simulations of accurate model of the electrical drive and genetic algorithms. Hence, no rough approximations or complex analytical calculations are performed to suitably design the inverter output filter. The method was validated by means of various tests performed on two different induction motor drives, considering some significant design constraint scenarios.